Comparison of lipase-transesterified blend with some commercial solid frying shortenings in Malaysia - Chu, B. S.; Ghazali, H. M.; Lai, O. M.; Che Man, Y. B.; Yusof, S.; Tee, S. B.; Yusoff, M. S. A. (Wiley, 2001)
A transesterified experimental solid frying shortening was prepared from a palm stearin/palm kernel olein blend at 1:1 ratio (by weight) by using Rhizomucor miehei lipase at 60°C for 6 h. The fatty acid (FA) and triacylglycerol compositions, polymorphic forms, melting and cooling characteristics, slip melting point (SMP), and solid fat content (SFC) of the transesterified blend were then compared with five commercial solid frying shortenings (three domestic and two imported) found in Malaysia. All the domestic shortenings contained nonhydrogenated palm oil or palm olein and palm stearin as the hard stock, whereas the imported frying shortenings were formulated from soybean oil and cottonseed oil and contained high levels of β′ crystals. Trans FA were also found in these samples. The lipase-transesterified blend was found to be more β′-tending than the domestic samples. The SMP of the transesterified blend (47.0°C) fell within the range of the domestic samples (37.8-49.7°C) but was higher than the imported ones (42.3-43.0°C). All samples exhibited similar differential scanning calorimetry cooling profiles, with a narrow peak at the higher temperatures and a broad peak at the lower temperatures, even though their heating thermograms were quite different. Imported samples had flatter SFC curves than both the experimental and domestic samples. The domestic samples were found to have better workability or plasticity at higher temperatures than the imported ones, probably because they were formulated for a tropical climate.